From black holes to flux throats: Polarization can resolve the singularity. Issue 4 (9th March 2016) - Cohen‐Maldonado, Diego; Diaz, Juan; Van Riet, Thomas; Vercnocke, Bert
Abstract : Supersymmetry‐breaking is a key ingredient for string theory models to be phenomenologically viable. We review the strong analogy in the physics and methods used for describing non‐supersymmetric flux vacua and non‐supersymmetric black holes in string theory. We also show how the polarized state could be the key to describing a well‐behaved back‐reaction of anti‐branes in flux backgrounds, shedding a new light on a recent debate in the literature.